CTAS: a CT score to quantify disease activity in pulmonary sarcoidosis. Issue 12 (27th July 2016) - Benamore, Rachel; Kendrick, Yvonne R; Repapi, Emmanouela; Helm, Emma; Cole, Suzanne L; Taylor, Stephen; Ho, Ling-Pei
Abstract : Background: A major gap in the management of sarcoidosis is the lack of accessible and objective methods to measure disease activity. Since 90% of patients have pulmonary involvement, we explored if a disease activity score based on thoracic CT scans could address this clinical issue. Methods: High-resolution CT scans from 100 consecutive patients with sarcoidosis at a regional sarcoidosis service were scored for extent of CT abnormalities known to relate to granuloma or lymphocytic infiltration from published CT-pathological studies. These individual abnormality scores were then correlated against serum ACE, sIL-2R and change in FVC to identify CT abnormalities that reflect contemporaneous disease activity. The sum of these scores, or CT A ctivity S core (CTAS), was then validated against FVC response to treatment. Findings: CT extent scores for nodularity, ground-glass opacification, interlobular septal thickening and consolidation correlated significantly with at least one of the disease activity parameters and were used to form CTAS. CTAS was found to predict FVC response to treatment at 1 year and was highly reproducible between radiologists. An abbreviated CTAS (aCTAS), constructed from presence or absence of the four CT abnormalities, also showed significant correlation with FVC response to treatment. CTAS and aCTAS also correlated with response to treatment in the fibrotic subgroup. Interpretation: CTAS provides a concept for an objective and reproducible CT scoring method to quantify disease activity in sarcoidosis. The score can potentially be used to stratify patients according to disease activity, determine response to treatment and establish if fibrotic sarcoidosis is active.